2020
DOI: 10.1002/jcla.23285
|View full text |Cite
|
Sign up to set email alerts
|

Revision of serum ALT upper limits of normal facilitates assessment of mild liver injury in obese children with non‐alcoholic fatty liver disease

Abstract: Background The serum alanine aminotransferase (ALT) level is a critical parameter for evaluating liver injury in non‐alcoholic fatty liver disease (NAFLD). However, the currently accepted upper limits of normal (ULN) for serum ALT (ULN‐ALT) are debated, as they may be excessively high. Methods A total of 1638 children aged 6‐16 years, comprising 507 children with normal BMI (500 healthy children and 7 children with NAFLD), 199 overweight children, and 932 obese children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…34 ALT is an indicator of hepatocyte injury. 35 Compared to the NC group, serum ALT levels increased significantly in the MC group ( P < 0.001, Fig. 5a), suggesting hepatocyte damage in the MC group due to lipid toxicity.…”
Section: Discussionmentioning
confidence: 90%
“…34 ALT is an indicator of hepatocyte injury. 35 Compared to the NC group, serum ALT levels increased significantly in the MC group ( P < 0.001, Fig. 5a), suggesting hepatocyte damage in the MC group due to lipid toxicity.…”
Section: Discussionmentioning
confidence: 90%
“…The search identified 735 references and 127 papers were selected for full‐text review. Finally, 31 articles 14‐44 describing 33 study populations fulfilled the criteria and included in the systematic review and pooled analysis (Figure 1). All the articles were published after 2004, and before April 28, 2021.…”
Section: Resultsmentioning
confidence: 99%
“…The features of the 31 studies 14‐44 were provided in Table 1. Eighteen studies in Eastern Asia (15 from China, two from Japan, one from Korea), 11 studies in Western Asia (five from Iran, five from Turkey, one from Israel) and two studies in Southern Asia (two from India).…”
Section: Resultsmentioning
confidence: 99%
“…However, increased scholars at home and abroad have suggested that children's ALT threshold in screening NAFLD should be lower than adults'. Lu et al ( 11 ) revised the serum ULN-ALT (25 U/L for males and 20 U/L for females), showing that the prevalence of NASH in children in China may be underestimated. NASH is a subtype of NAFLD that can develop into cirrhosis, hepatocellular carcinoma, and even death ( 12 ), and children usually suffer more severe NAFLD than adults ( 13 ), among all about 15%were accompanied with NASH and associated cirrhosis when diagnosed with NAFLD ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%